The influence of discipline and work experience on the achievement of employees in Dinas Pariwisata dan Kebudayaan kabupaten Karo - JURNAL DARMA AGUNG LPPM; Lamminar Hutabarat (JURNAL GLOBAL MANAJEMEN, 2021)
This study aims to determine the effect of discipline and work experience partially or simultaneously on the work performance of employees at the Karo Regency Tourism and Culture Office. The research method used was quantitative, with 41 respondents. Methods of data collection using documentation research methods and field research methods. Data were analyzed using multiple linear regression analysis. Hypothesis testing is done by using the t test and the F test. To see the influence of the independent variables on the dependent variable, the coefficient of determination test is used. The results show that the regression equation obtained is: Y = 8,442+ 1,236 X₁ + 0,365 X₂, meaning that if it is assumed that discipline (X1) and work experience (X2) are 0, then the work performance value (Y) is constant or 8,442 and an increase of 1 Discipline and work experience variable units will result in an increase in work performance of 8,442. Discipline has a positive and significant effect on employee work performance. This can be proven by the known value of the t value (7.023) is greater than the t table value (2.022). Besides that, the significance value of 0.000 is less than 0.05. Work experience has no effect on employee work performance. This can be proven by the t value (1,300) is smaller than the t table value (2,022). In addition, the significance value is 0.201 which is greater than 0.05. Discipline and work experience simultaneously affect the work performance of employees at the Karo Regency Tourism and Culture Office. This result is known from the calculated F value (33.421) greater than the F table value (3.24), and the significance value of 0.000 is less than 0.05. The Adjusted R Square value is 0.618, which means that the dependent variable (employee work performance) is influenced by the combination of discipline variables and work experience of 61.8%, while the remaining 38.2% (100% - 61.8%) is influenced by other factors not examined in this study.